Analisis Kadar Glukosa Darah Puasa dengan Laju Filtrasi Glomerulus pada Pasien Diabetes Mellitus Tipe II Terindikasi Mikroalbuminuria - Nofri Eka Yuliandi; Aulia Mutiara Hikmah (Jurnal Medical Laboratory, 2024)
Type II diabetes mellitus patients generally have high fasting blood glucose levels. Continuously high fasting blood glucose levels can cause damage to the kidneys and increase albumin levels in the urine. When albumin levels rise there can be a risk of high glomerular filtration rate and cause the risk of diabetic nephropathy. The aim of this study was to determine the results of analysis of fasting blood glucose levels and glomerular filtration rate in type II diabetes mellitus patients with indications of microalbuminuria. This research uses a correlative method with a purposive sampling technique in accordance with the inclusion criteria and exclusion criteria. The sample obtained was 110 research respondents using a cross sectional study approach. The results of the study showed that the correlation carried out with Spearman's Rho between the glomerular filtration rate and fasting blood glucose levels had a p-value of 0.081 so that the p-value was > 0.05, it could be concluded that there was no relationship between glomerular filtration rate and fasting blood glucose levels.